The cowboy meets his match - Clare, Jessica (Clare, Jessica. Wyoming cowboys., 2020)
"Single father Henry "Hank" Watson is a fresh transplant from Alaska to Painted Barrel, Wyoming. He doesn't want anything more from life than to put in a good day's work, then go home to his daughter, Libby. But when Libby needs some emergency work done on her curls thanks to a gum incident, Hank's out of his depth. He takes his daughter into town where he meets Becca, the local salon owner."--from publisher's website.